Pendampingan Penerapan Ekonomi Sirkular sebagai Tindak Lanjut Program Pengelolaan Sampah dan Limbah VCO pada KWT Al-Ummahat di Desa Lendang Nangka, Lombok Timur - Ade Rezkika Nasution; Mutiara Mita Kasia; Mohammad Alwi Shahab; Shelly Sylvia Agustina; Farah Ainun Jamil (Universitas Mataram, 2026)
This community service activity aims to be a follow-up to previous training, namely Management of Household Waste and VCO Waste produced by the Al Ummahat Women's Farmers Group (KWT) in Lendang Nangka Village, East Lombok Regency. Through assistance with circular economy principles, it is hoped that it can encourage the formation of business units based on sustainable waste processing at the KWT level. Implementation methods include intensive counseling and assistance that integrates three main pillars, namely environmental, economic and social aspects, as mandated in the Sustainable Development Goals (SDGs), especially SDG 1 (no poverty), SDG 12 (responsible consumption and production), SDG 13 (handling climate change), and SDG 15 (land ecosystem). The results of the activities showed a significant increase in participants' capacity, including understanding the concept of a circular economy (average increase of 52.4%), skills in processing organic waste into compost and organic liquid fertilizer (48.8%), as well as skills in recycling inorganic waste into marketable craft products (55.2%). This activity contributes to strengthening household economic resilience and environmental sustainability in Lendang Nangka Village.